Policy reaction to hidden spaces on the urban periphery: the case of backyard accommodation in Dube Township, Johannesburg - Chabalala, Tshepo Clement (My University, 2021)
Backyard rental accommodation is not covered by a policy that addresses the issues of the market and the sector does not receive any support from the state. This study investigates backyard rental accommodation. The main argument is that backyard accommodation provides beneficiaries or property owners (landlords) of government-subsidized housing with opportunities to improve their economic situation, material and social well-being and allows them to improve their houses, thereby improving their quality of life. Backyard accommodation provides affordable, flexible accommodation and social stable environments to tenants. Moreover, it represents a unique mixture of informal and formal land-tenure modes that has not yet been recognized in policy formulation for housing. Measures taken by authorities and policy makers rather condemn and discourage the practice of backyard rental accommodation instead of supporting it as an aspect of housing that can help realize housing as an asset. The reasoning is that backyard rental accommodation increases the density of the houses and households beyond which they were created for and puts pressure on infrastructure and other several implications that requires careful management and coordination. The overall contribution of this research is to understand the processes of informality and the reaction from government policy on backyard accommodation on the urban periphery. The research study focuses on the case of backyard accommodation in Dube Township, Johannesburg. Various qualitative research methods are adopted for this research including desktop analysis of grey literature, and data collection methods such as interviews and questionnaires. The study took place in 2019. There has been a shift to greater understanding and acknowledgement of the role backyard accommodation plays and initial attempts have been made to support it. The findings and synopsis of the study show that there is a direct relationship between the landlords and tenants and that there are common drivers of supply and demand of backyard accommodation. The study makes recommendations such as awareness campaigns, government’s acknowledgement and area-based municipal policy approach for interventions and development regarding backyard accommodation
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Urban Studies (Urban Politics and Governance), School of Architecture and Planning, 2021